2009
DOI: 10.1111/j.1551-2916.2009.03273.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure–Ionic Conductivity Relationships in Doped Ceria Systems

Abstract: In the past, it has been suggested that the maximum ionic conductivity is achieved in ceria, when doped with an acceptor cation that causes minimum distortion in the cubic fluorite crystal lattice. In the present work, this hypothesis is tested by measuring both the ionic conductivity and elastic lattice strain of 10 mol% trivalent cation‐doped ceria systems at the same temperatures. A consistent set of ionic conductivity data is developed, where the samples are synthesized under similar experimental condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

23
153
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(178 citation statements)
references
References 28 publications
23
153
1
1
Order By: Relevance
“…Fe-doped Ln (Ln ¼ La series elements) SrO 3 ) are reported to show a higher stability than Co/Ni-based oxides under a reducing or CO 2 atmosphere 26 and show good p-type electronic conductivity; 27,28 (ii) in a recent study, covering a large number of 10 atm% rare earth doped cerias, synthesized under similar conditions, Nd-doping ceria is reported to exhibit the highest ionic conductivity. 29 (iii) Based on the common ion effects, which was dened as the suppression of dissociation of a weak electrolyte containing a common ion, we chose the same element (Nd) in both OIC and EC phases in order to reduce the element diffusion between the two phases; 30 (iv) the concentration of the highly EC component NSFO in the dual phase materials was chosen to be 40 wt% in order to guarantee a continuous electron transport in a percolation network.…”
Section: Introductionmentioning
confidence: 99%
“…Fe-doped Ln (Ln ¼ La series elements) SrO 3 ) are reported to show a higher stability than Co/Ni-based oxides under a reducing or CO 2 atmosphere 26 and show good p-type electronic conductivity; 27,28 (ii) in a recent study, covering a large number of 10 atm% rare earth doped cerias, synthesized under similar conditions, Nd-doping ceria is reported to exhibit the highest ionic conductivity. 29 (iii) Based on the common ion effects, which was dened as the suppression of dissociation of a weak electrolyte containing a common ion, we chose the same element (Nd) in both OIC and EC phases in order to reduce the element diffusion between the two phases; 30 (iv) the concentration of the highly EC component NSFO in the dual phase materials was chosen to be 40 wt% in order to guarantee a continuous electron transport in a percolation network.…”
Section: Introductionmentioning
confidence: 99%
“…23 However, higher activation energy values for strained films clearly indicate an expected increase in migration and association enthalpies related to oxygen vacancy diffusion for the strained lattice when compared to the strain-free one. 14 In polycrystalline CGO, the grain boundary acts as blocking surface and the resistance offered to oxygen ionic conduction is larger to cross the grain boundary than to through bulk/grain interior. Minimizing the grain boundary network via depositing epitaxial films leads to reduce resistance contribution from grain boundaries which results in the ionic conductivity enhancement.…”
Section: -2mentioning
confidence: 99%
“…In another report, it has been shown that lattice-strain induced in polycrystalline ceria by doping it with trivalent cations (Nd 3þ and Nd þ3 /Sm 3þ as compared to Gd þ3 ) not only enhances the ionic conductivity but also changes the activation energy. [14][15][16][17] However, the information available on epitaxy and its influence on the electrical properties of CGO thin films is limited. The major difficulty in evaluating and explaining the electrical properties of CGO thin films is to separate the ionic conductivity from the total measured conductivity.…”
mentioning
confidence: 99%
“…Solid electrolytes are the most important and indispensable component of SOFCs that govern the performance and to a large extent the design of the system [3]. Currently, the yttria-stabilized zirconia (YSZ) is the commonly applied electrolyte for SOFCs, however, its high operating temperature (800-1000 ℃) leads to a severe criteria for other construction materials, as well as short service times [4,5].…”
Section: Introductionmentioning
confidence: 99%